Does Abiotic Host Stress Favour Dothideomycete-Induced Disease Development? - Laura Röhrig; Francois Dussart (Plants, 2022)
Dothideomycetes represent one of the largest and diverse class of fungi. This class exhibits a wide diversity of lifestyles, including endophytic, saprophytic, pathogenic and parasitic organisms. Plant pathogenic fungi are particularly common within the Dothideomycetes and are primarily found within the orders of Pleosporales, Botryosphaeriales and Capnodiales. As many Dothideomycetes can infect crops used as staple foods around the world, such as rice, wheat, maize or banana, this class of fungi is highly relevant to food security. In the context of climate change, food security faces unprecedented pressure. The benefits of a more plant-based diet to both health and climate have long been established, therefore the demand for crop production is expected to increase. Further adding pressure on food security, both the prevalence of diseases caused by fungi and the yield losses associated with abiotic stresses on crops are forecast to increase in all climate change scenarios. Furthermore, abiotic stresses can greatly influence the outcome of the host-pathogen interaction. This review focuses on the impact of abiotic stresses on the host in the development of diseases caused by Dothideomycete fungi.